2020
DOI: 10.2147/ijn.s245801
|View full text |Cite
|
Sign up to set email alerts
|

<p>Functionalized Graphene Nanoparticles Induce Human Mesenchymal Stem Cells to Express Distinct Extracellular Matrix Proteins Mediating Osteogenesis</p>

Abstract: Purpose: The extracellular matrix (ECM) labyrinthine network secreted by mesenchymal stem cells (MSCs) provides a microenvironment that enhances cell adherence, proliferation, viability, and differentiation. The potential of graphene-based nanomaterials to mimic a tissue-specific ECM has been recognized in designing bone tissue engineering scaffolds. In this study, we investigated the expression of specific ECM proteins when human fat-derived adult MSCs adhered and underwent osteogenic differentiation in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 66 publications
5
33
0
Order By: Relevance
“…Moreover, GDs could regulate the osteogenic differentiation of stem cells from different sources because they could provide stem cells with a unique physical framework comparable to natural extracellular matrix (ECM). [123][124][125] For example, Newby et al 123 prepared GO nanoparticles with oxygen content of 6-10%, then co-cultured them with human mesenchymal stem cells (MSCs), and evaluated the effect of graphene nanoparticles on osteogenic differentiation of these stem cells by alizarin red staining and quantitative analysis. The results showed that the calcium content of MSCs co-cultured with GO nanoparticles was significantly higher than that of cells on the control surface.…”
Section: Improving Functions Of Bone-related Cells In Vitro and Bone mentioning
confidence: 99%
“…Moreover, GDs could regulate the osteogenic differentiation of stem cells from different sources because they could provide stem cells with a unique physical framework comparable to natural extracellular matrix (ECM). [123][124][125] For example, Newby et al 123 prepared GO nanoparticles with oxygen content of 6-10%, then co-cultured them with human mesenchymal stem cells (MSCs), and evaluated the effect of graphene nanoparticles on osteogenic differentiation of these stem cells by alizarin red staining and quantitative analysis. The results showed that the calcium content of MSCs co-cultured with GO nanoparticles was significantly higher than that of cells on the control surface.…”
Section: Improving Functions Of Bone-related Cells In Vitro and Bone mentioning
confidence: 99%
“…Therefore, we performed a screen for the expression of several adhesive marker genes, such as Fn1, Vcl, Cd44, and Icam1, in ST2 and MC3T3-E1 cells grown on the collagen-based scaffolds. Fn1 gene encodes fibronectin, which is a ubiquitously expressed, non-collagenous extracellular matrix (ECM) protein with a major role in regulating cell adhesion and differentiation ( Newby et al, 2020 ). Vcl encodes vinculin, which is an essential component of the focal adhesions and associated with both cell-cell and cell-matrix interactions ( Bays and DeMali, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…GO-filmed substrates also intensified the differentiation of mouse ESCs to the hematopoietic lineage [ 15 ]. Growing evidence has indicated that a graphene surface provides a biocompatible nanoscale to accelerate the differentiation of human mesenchymal stem cells (hMSCs) into a bone cell specification without cellular toxicity [ 8 , 16 , 17 ]. GO-incorporated poly (lactic-co-glycolic acid) (PLGA) nanofiber structures also enhance the proliferation and osteogenic differentiation of hMSCs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%